Trends in an increased dependence towards hydropower energy utilization—a short review. Issue 1 (1st January 2019) - Chala, Girma T.; Ma'Arof, M. I. N.; Sharma, Rakesh
Abstract: Over the past few decades, fossil fuels replacements have shown leaps and bounds of progressions. Hence, various nations have initiated the adoption of biomass energy, solar energy, wind energy and hydropower energy. Yet, these currently developing technologies have constantly faced dual pressure from both the economic growth and environmental protection. Hydropower has become a key candidate for considerable utilization in various countries due to its numerous social, economic and environmental benefits. In this paper, a short review was carried out to analyse the development of various hydropower plants and compare its utilization over the conventional fossil fuels. The main setback for the adoption of this technology is that large hydropower plant demands for huge deforestation. This would direly result in the destruction of critical ecosystems, migration of large population at downstream and other catastrophic outcomes such as flash floods and landslides. However, this singular setback could be alleviated with the utilization of small or micro hydropower plant. This technology, in particular, was found to have minimal destruction effects to the environment and is able to produce affordable energy to the rural areas as it has proven in many countries.